Virtual Reality-Assisted Historical Empathy-Based Multicultural Learning Model to Enhance High School Students' Empathy - Sumargono, Sumargono; Sinaga, Risma Margaretha; Ariyani, Farida; Rini, Riswanti (Universitas Islam Negeri Raden Intan Lampung, 2024)
Multicultural learning is widely used in high school history education. This study aims to determine the effectiveness of a historical empathy-based multicultural learning model (MHE), assisted by virtual reality, to enhance student empathy. The research was conducted using the Research and Development (R&D) method with the Borg and Gall development model, consisting of ten steps. Data collection instruments included interviews, questionnaires, tests, observations, and Focus Group Discussions. Data analysis involved examining product validity, practicality, and effectiveness. The results showed that the final assessment of the MHE learning model obtained a content validity percentage of 93.40% and a construct validity percentage of 92%. The final assessment of the teaching module achieved a rate of 93.39%. The final assessment of the virtual reality learning media obtained a percentage of 92.10%. Thus, the learning models, textbooks, teaching modules, and virtual reality learning media are declared